2017
DOI: 10.1186/s12879-017-2394-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing real-time Zika risk in the United States

Abstract: BackgroundConfirmed local transmission of Zika Virus (ZIKV) in Texas and Florida have heightened the need for early and accurate indicators of self-sustaining transmission in high risk areas across the southern United States. Given ZIKV’s low reporting rates and the geographic variability in suitable conditions, a cluster of reported cases may reflect diverse scenarios, ranging from independent introductions to a self-sustaining local epidemic.MethodsWe present a quantitative framework for real-time ZIKV risk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…ZIKV is a member of the Flaviviridae family of viruses, which are transmitted to humans by mosquitoes and ticks and are responsible for millions of infections annually. ZIKV has historically been restricted to tropical/sub-tropical regions but it has now reached the Southern USA 2 . Recent studies have demonstrated that ZIKV infects and predominantly damage human neural precursors; however, the cellular and molecular mechanisms of ZIKV pathogenesis remain poorly understood 3 6 .…”
Section: Introductionmentioning
confidence: 99%
“…ZIKV is a member of the Flaviviridae family of viruses, which are transmitted to humans by mosquitoes and ticks and are responsible for millions of infections annually. ZIKV has historically been restricted to tropical/sub-tropical regions but it has now reached the Southern USA 2 . Recent studies have demonstrated that ZIKV infects and predominantly damage human neural precursors; however, the cellular and molecular mechanisms of ZIKV pathogenesis remain poorly understood 3 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised that several other locations in the contiguous US were at risk of ZIKV transmission, thus triggering a number of studies aimed at identifying populations at highest risk of local transmission [ 10 20 ]. In particular, detailed studies based on environmental suitability, epidemiological factors, and travel-related case importations have been used to estimate the risk for specific counties in the US [ 21 , 22 ]. In this study, we quantify the risk of local ZIKV transmission by using a data-driven stochastic and spatial epidemic model accounting for seasonal, environmental, and detailed population data.…”
Section: Introductionmentioning
confidence: 99%
“…Models may be used to infer R 0 as well as forecast changes in R 0 that could drive transitions in epidemic dynamics, such as the shift from sporadic outbreaks to sustained chains of transmission. Example: assessing real-time Zika risk in Texas 90 .…”
Section: Box 1 | Modelling Infectious Disease Transmission For Evidenmentioning
confidence: 99%
“…In contrast to univariate sensitivity analyses, uncertainty analysis simultaneously samples from empirical-or expert-informed distributions for many or all input parameters. Collaboration between modellers and disease experts is thus instrumental to ensuring the biological plausibility of these parameter distributions 90,91 . The uncertainty analysis produces both a central point estimate and a range for each outcome, a combination which can inform stakeholders about the best-case and worst-case scenarios as well as the likelihood that an intervention will be successful [92][93][94] .…”
Section: Sensitivity and Uncertainty Analysismentioning
confidence: 99%